Analisis Sistem House Load Dalam Menunjang Kehandalan Penyaluran Listrik di PLTDG Pesanggaran - I Wayan Sugara Yasa; Guntara Nur; Made Asna (Universitas Pendidikan Nasional, 2021)
The rapid and continuous growth of electricity today makes the availability of electricity must continue to increase as well. However, sometimes an imbalance between the capacity of the generating unit and the load on the power grid system can cause a decrease/increase in the frequency of the generating unit system, including the generation side, which under certain conditions can cause the generating unit to die. If the generating units are shutdown at the same time/simultaneously it can result in a blackout on the system. The house load operation mode on the power generation unit is one of the scenarios that can be applied to speed up the recovery process during a blackout. In this study, a house load test was carried out on one of the generating units. The methodology used is to conduct direct testing on the PLTDG Block 4 Unit 11 Pesanggaran. The results of this test the unit has successfully carried out a house load test with a time of 30 minutes from the 150 kV network voltage loss unit so that the house load operation mode on the PLTDG Block 4 Unit 11 Pesanggaran generator unit can accelerate the efficiency of synchronization back to the network between 73.26% to 88.31% produces an efficiency of 15.05%. Besides being able to increase the reliability of the distribution of the electric power system, the application of the house load operation mode on the generating unit can provide potential economic benefits of Rp. 1,690,804,988.,